Railway Signaling Relay Temperature Field Analysis and Experimental Verification - LI Wenhua; MA Sining; SHEN Peigen (机车电传动)
Mathematical model of the railway signaling relay was established under the effect of heat-electricity coupling. Railway signaling relay temperature field variation under different temperature was analyzed with the finite element model considering environment temperature, and impact of the temperature was taken into consideration in the process of simulation calculation. It indicated that relay temperature rise decreased with the environmental temperature rise; Contact temperature from room temperature to the steady state temperature exponentially raised, and the thermal time constant of the resistance was calculated to deduce the theory of contact resistance temperature rise curve; Temperature had a greater impact on the contact, and contact temperature and environmental temperature were positively correlated.